Characterization of thermally modified short and long rotation teaks and the effects on coatings performance - Lisa Adina Pratiwi; Wayan Darmawan; Trisna Priadi; Béatrice George; André Merlin; Christine Gérardin; Stéphane Dumarçay; Philippe Gérardin (Maderas: Ciencia y Tecnología, 2019)
Many wood processing industries use short rotation teak, which has lower quality especially in durability and dimensional stability. Heat treatment is an eco-friendly method to improve dimensional stability and durability of wood. The objectives of the study were to investigate the effects of thermal modification on chemical composition, colour, dimensional stability and durability as well as coating’s performance after accelerated weathering of short and long rotation teak for exterior utilization. In this study, the samples were heated in oven at 220 °C for 20 h under nitrogen atmosphere. Results showed that independently of growth conditions teak woods underwent hemicelluloses degradation and an increase of lignin content after heat treatment. Extractives contents were lower in short rotation than in long rotation teak, and decreased in all cases after heat treatments. Dimensional stability was considerably improved as indicated by anti-swelling efficiency values of 64.9% and 58.9% for short and long rotation teak, respectively. Heated teak woods were more resistant against Trametes versicolor and the durability of short-rotation teak increased from moderate to very durable. Coatings on heat treated teaks had better bonding quality and better photo-stability when compared to unheated. Heated short rotation teak could be considered for exterior application.